2015
DOI: 10.1039/c5ra12342a
|View full text |Cite
|
Sign up to set email alerts
|

RuO2/MWCNT/ stainless steel mesh as a novel positive electrode in vanadium redox flow batteries

Abstract: The present work describes the preparation and electrochemical characterization of RuO2/MWCNT/Stainless Steel Mesh (SSM) electrode as compared with a MWCNT/SSM electrode in the positive half-cell of a Vanadium Redox Flow Battery (VRFB). The electrochemical characterization of prepared electrode was carried out using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge/discharge procedures. The electrochemical activity of MWCNT/SSM modified with RuO2 as positive electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…RuO 2 deposited electrochemically on MWCNT attached with a binder (PVC) to a stainless steel mesh has been proposed as a positive electrode in a VRFB [431]. Corrosion rate of the steel was considered to be acceptable.…”
Section: Metal Oxide Depositsmentioning
confidence: 99%
“…RuO 2 deposited electrochemically on MWCNT attached with a binder (PVC) to a stainless steel mesh has been proposed as a positive electrode in a VRFB [431]. Corrosion rate of the steel was considered to be acceptable.…”
Section: Metal Oxide Depositsmentioning
confidence: 99%
“…RuO 2 and other tetravalent ruthenium oxides are reported to be suitable materials for electrode components in many electrochemical systems. [ 126 ] Thus, Gobal et al [ 126 ] suggested the use of RuO 2 to enhance the V(IV)/V(V) reaction and fabricated a catalyst by incorporating the oxide into MWCNTs supported by a stainless steel mesh (SSM) substrate. The RuO 2 ‐MWCNT completely covered the surface of the SSM substrate to prevent its corrosion by the electrolyte.…”
Section: All‐vanadium Rfbmentioning
confidence: 99%
“…Half‐cell galvanostatic charge/discharge of V(IV)/V(V) redox reaction on RuO 2 ‐MWCNT‐SSM electrode for the first and 10 th days. Extracted with permission from [ 126 ] .…”
Section: All‐vanadium Rfbmentioning
confidence: 99%
“…For example, the deposited noble metal (Pt , and Ir) catalysts exhibit high activity for positive or negative redox reactions, but these metals are expensive and prone to gas evolution. Inexpensive metal (Bi) or metal oxides (Nb 2 O 5 , Mn 3 O 4 , , TiO 2 , RuO 2 , and WO 3 ) have been used as substitutes for noble metal catalysts to enhance the activity of vanadium ion reaction. However, the electrocatalytic activity of the abovementioned electrodes is inhibited by the nonhomogeneous distribution and low activity caused by the large size, and their preparation processes are tedious and intricate.…”
Section: Introductionmentioning
confidence: 99%